Understanding patients' satisfaction with physician assistant/associate encounters through communication experiences: a qualitative study in acute hospitals in England - Francesca Taylor; Mary Halter; Vari M Drennan (BMC, 2019)
Abstract Background Physician assistants/associates (PAs) are a recent innovation in acute hospital teams in England and many other countries worldwide. Although existing evidence indicates generally high levels of patient satisfaction with their PA hospital encounters, little is known about the factors associated with this outcome. There is a lack of evidence on the process of PA-patient communication in hospital encounters and how this might influence satisfaction. This study therefore aimed to understand patients' satisfaction with PA acute hospital encounters through PA-patient communication experiences. Methods A qualitative study was conducted among patients and representatives of patients seen by or receiving care from one of the PAs working in acute hospital services in England. Semi-structured interviews were undertaken face-to-face with study participants in the hospital setting and shortly after their PA encounter. Data were coded and analysed using thematic analysis. The study was framed within a theoretical model of core functions of medical encounter communication. Results Fifteen patients and patient representatives who had experienced a PA encounter participated in interviews, across five hospitals in England. Four interrelated communication experiences were important to participants who were satisfied with the encounter in general: feeling trust and confidence in the relationship, sharing relevant and meaningful information, experiencing emotional care and support, and sharing discussion on illness management and treatment. However, many participants misconceived PAs to be doctors, raising a potential risk of reduced trust in the PA relationship and negative implications for satisfaction with their PA encounter. Participants considered it beneficial that patients be informed about the PA role to prevent confusion. Conclusions PA encounters offer a constructive example of successful clinician-patient communication experiences in acute hospital encounters from the patient's perspective. Study participants were generally naïve to the PA role. Hospital services and organisations introducing these mid-level or advanced care practitioner roles should consider giving attention to informing patients about the roles.